Strengthening Legal Protection for Traditional Cultural Expressions in North Sulawesi: A Community-Based Approach to Prevent Commercial Misappropriation - Maskun Maskun; Budiyanto Budiyanto; Muhammad Saleh Tajuddin; Muhammad Mutawalli Mukhlis; Ahmad Masum (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement) JPHI, 2026)
This community service aims to strengthen the legal protection of Traditional Cultural Expressions (TCEs) in North Sulawesi against unauthorized commercial utilization by improving stakeholders' understanding of communal intellectual property (IP) protection and enhancing readiness for inventory and documentation. The program adopted a participatory legal community service approach involving needs identification, legal counseling, interactive discussions, and evaluation with local stakeholders. The needs assessment identified two major challenges: incomplete inventory and documentation of TCEs for communal intellectual property registration and the absence of local mechanisms governing permission and benefit-sharing for commercial utilization. To address these issues, the program produced three practical outputs: a shared action pathway for communal IP registration, a simplified inventory and documentation checklist, and policy recommendations supporting local regulations on permission and benefit-sharing. The findings indicate that legal counseling combined with stakeholder participation can improve institutional readiness for communal IP protection while providing an operational basis for strengthening preventive legal protection. The program also highlights the importance of developing regional regulations or a sui generis legal framework to ensure legal certainty, equitable benefit-sharing, and the sustainable preservation of Traditional Cultural Expressions in North Sulawesi. This aligns with Sustainable Development Goals (SDGs) 17: Partnerships for the Goals.